2018
DOI: 10.1002/lary.27155
|View full text |Cite
|
Sign up to set email alerts
|

Nodal response after 46 Gy of intensity‐modulated radiotherapy is associated with human papillomavirus–related oropharyngeal carcinoma

Abstract: 4. Laryngoscope, 128:2333-2340, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a phase III study from the Trans-Tasman Radiation Oncology Group (TROG 02.02), 13.7% of 102 p16-positive patients were HPV negative [9]. Because the prognosis of HPV-mediated OPSCC is fair, it is possible that even if treatment intensity is lowered, the prognosis will not worsen [10, 11]. These de-escalation studies are fascinating in terms of a paradigm shift in OPSCC therapy, and we also consider that there might be a subgroup without HPV DNA in HPV-mediated OPSCC defined by p16 overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…In a phase III study from the Trans-Tasman Radiation Oncology Group (TROG 02.02), 13.7% of 102 p16-positive patients were HPV negative [9]. Because the prognosis of HPV-mediated OPSCC is fair, it is possible that even if treatment intensity is lowered, the prognosis will not worsen [10, 11]. These de-escalation studies are fascinating in terms of a paradigm shift in OPSCC therapy, and we also consider that there might be a subgroup without HPV DNA in HPV-mediated OPSCC defined by p16 overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…Although a small number of previous studies have reported outcomes following an SBRT boost, these have been in the setting of more advanced and/or inoperable disease with a minority of patients with oropharynx cancer, precluding meaningful comparison . Of note, during the time frame of the study, p16 testing was selective and not on a routine basis; based on previous research in Dutch patients with OPSCC, the true incidence of human papilloma virus (HPV)‐associated OPSCC in the study population is approximately 40%‐50% …”
Section: Discussionmentioning
confidence: 99%
“…6,7 Of note, during the time frame of the study, p16 testing was selective and not on a routine basis; based on previous research in Dutch patients with OPSCC, the true incidence of human papilloma virus (HPV)-associated OPSCC in the study population is approximately 40%-50%. [17][18][19] Previous analyses of the location of recurrences with respect to RT fields have reported nearly all local recurrences to occur within the site of the previous GTV, suggesting radioresistance as the underlying mechanism. [1][2][3]8,9 Here, we observed a shift in this classic recurrence pattern: only 76% of local recurrences occurred with COM in-field (n = 12 within GTV and n = 1 within CTV), whereas 24% occurred out-of-field (n = 4 outside PTV).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations